Assessment of serum and urine ghrelin levels in patients with acute stroke - Seyhanli, Eyyup Sabri; Lok, Ugur; Gulacti, Umut; Buyukaslan, Hasan; Atescelik, Metin; Yildiz, Mustafa; Aydin, Suleyman (E-Century Publishing Corp, 2015)
Introduction: Ghrelin is a novel brain-gut peptide hormone consisted of 28 amino-acid. In the plasma, it exists in two major molecular forms, acylated and des-acyled ghrelin, filtered in glomeruli or secreted by nephrons. Primary biological effects of hormones are regulating appetite, foods intake and energy metabolism. We investigated the changing and relationships between serum and urine ghrelin levels in acute stroke patients to provide more information whether diagnostic parameter. Methods: Thirty acute stroke patients and thirty consecutive volunteers included in study prospectively. To analyze serum and urine ghrelin levels, at the time of diagnose, all of participant blood and fresh urine (1 ml serum, 2 ml urine respectively) samples were obtained. Serum ghrelin levels analyzed ELISA technique, and urine ghrelin levels studied by validation technique. To compare quantitative data student's t test, and for qualitative data chi-square and Fisher's Exact Chi-square test was used. P<0.05 was considered statistically significant. Results: Urine acyl ghrelin levels found statistically significant between patient and control groups (P=0.001), but there were no statistically significant differences between both groups (P>0.05) in serum acyl gherelin, des-acyl ghrelin and urine des-acyle ghrelin levels. Conclusions: The results indicate that urine acyl ghrelin levels may be considered as a diagnostic parameter in acute ischemic stroke patients. Further studies delineating the mechanism of these observed results are warranted.
Keywords: Stroke; acute; ghrelin; serum; urine